Atención al usuario en el Centro de Salud Puertas Negras Distrito 12D01 ubicado en la cuidad de Babahoyo provincia de Los Ríos periodo 2023. - Gavilánez Loor, Lady Liliana (2024)
The present case study titled "User care at the Puertas Negras health center District 12D01 located in the city of Babahoyo province of Los Ríos Period 2023" aims to analyze the internal aspects that occur in the establishment to improve its efficiency that leads to more effective and safe high-quality care. To collect information, the methodology of direct interviews with the person in charge of the health center and surveys that were directed at users of the public establishment were used. After the deficiencies faced by the place are detected, it will be possible to apply immediate measures and strategies that improve the service provided to the user. These strategies will allow you to offer alternatives and considerations so that you can make informed decisions and thus have a clear action plan to implement the proposed solutions.